Method for producing titanium porous body
Patent Information
- Application Number
- JP2023149587
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
AI Technical Summary
【0015】 この発明のチタン多孔質体の製造方法によれば、切断箇所を良好な性状とし、比較的短時間のうちにチタン焼結体を様々な寸法·形状に切断することができる。
Smart Images

Figure 2025042519000001 
Figure 2025042519000002 
Figure 2025042519000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a sheet-like porous titanium body. [Background technology]
[0002] Porous titanium produced by sintering titanium powder or the like has air and liquid permeability due to its fine pores, and electrical conductivity. It also has high corrosion resistance due to the formation of a passive film on the surface.
[0003] Porous titanium bodies with such properties are being considered for use in porous transport layers (PTLs) in polymer electrolyte membrane (PEM)-type water electrolysis devices, which are in environments where corrosion may occur. In particular, hydrogen produced in PEM-type water electrolysis devices using electricity derived from renewable energy is called green hydrogen, and is expected to play a major role in accelerating efforts to realize a decarbonized society in recent years. Titanium sintered bodies obtained by sintering titanium powder or the like can be used for such porous titanium bodies.
[0004] When the titanium porous body is used in a porous transport layer of a solid polymer water electrolysis device, it may be necessary to cut the titanium porous body into various shapes according to the cells of the water electrolysis device.
[0005] Regarding the cutting of a porous metal body, Patent Document 1 describes "a method for producing a porous metal body, comprising a cutting step of cutting a long sheet-like porous metal body having a skeleton with a three-dimensional mesh structure in the longitudinal direction using two disk-shaped slit blades combined vertically, in which at least one of the two disk-shaped slit blades is pressed against the other slit blade in the cutting step, so that the blade tips of the two disk-shaped slit blades are in contact with each other." In an example of Patent Document 1, regarding the "porous metal body" to be cut, it is described that "a nickel porous metal body having a length of 200 m in the longitudinal direction A and a thickness of 1 mm was prepared. The nickel porous metal body had a skeleton with a three-dimensional mesh structure, an average pore diameter of 400 μm, and a porosity of 98%."
[0006] In the examples of Patent Document 2, it is stated that "an operator manually cuts a porous metal body (porosity 97%, thickness 1.4 mm, width 160 mm) made of nickel components." Patent Document 2 also states that "the cutting means is not particularly limited as long as it can cut the porous metal body, and can be a push cutter method with blades on both the top and bottom, or a method in which a disk-shaped blade moves in the width direction while rotating on a resin plate placed on the bottom, or any other method can be used, as the porous metal body has a high porosity, and can be easily cut." [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2020 / 039693 [Patent Document 2] JP 2008-170197 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described in Patent Documents 1 and 2, it is believed that a metal porous body made of nickel or the like having a high porosity can be cut with a cutter, knife, or the like.
[0009] On the other hand, a porous transport layer of a solid polymer water electrolysis device may require a sheet-like titanium porous body having a relatively thin thickness and low porosity. In this case, it is necessary to cut the titanium sintered body to the desired size and shape to obtain a titanium porous body having a size and shape suitable for the porous transport layer, but a titanium sintered body having a thin thickness and low porosity cannot be easily cut with a cutter or knife. This not only takes time to cut, but also makes it easy to form irregularities at the cut parts such as the edges of the titanium porous body after cutting. In addition, a cutter or knife has restrictions such as the cutting pattern being limited to a linear shape, and it is difficult to say that the titanium sintered body can be freely cut into any shape.
[0010] An object of the present invention is to provide a method for producing a porous titanium body that can cut a sintered titanium body into various sizes and shapes in a relatively short time while maintaining good quality at the cut portions. [Means for solving the problem]
[0011] As a result of intensive research, the inventors have found that so-called abrasive jet machining is effective for cutting titanium sintered bodies having a predetermined thickness and porosity. In particular, by using a powdered or particulate abrasive having a predetermined hardness and shape in the liquid sprayed toward the titanium sintered body to cut the titanium sintered body, the cut portion of the titanium porous body obtained after cutting can have good properties. Furthermore, abrasive jet machining can cut into any shape, such as a straight line or a curved line, and there is a high degree of freedom in the cutting mode. However, since the abrasive may remain in the titanium porous body after cutting, it is essential to adjust the composition so as not to adversely affect the subsequent use of the titanium porous body in a predetermined application.
[0012] The method for producing a titanium porous body of the present invention includes a cutting step in which a liquid containing an abrasive is sprayed toward a titanium sintered body to cut the titanium sintered body, wherein the titanium sintered body is in sheet form and has a thickness of 10 μm or more and 3000 μm or less and a porosity of 30% or more and 55% or less, and an abrasive used in the cutting step contains a total of 60 mass% or more of Si and / or Ti and O, and contains 5 mass% or less of Al, Fe, Ni, Mn, Cr and Cu, has a Mohs hardness of 4.5 or more and 9.0 or less, and an average circularity of 0.5 or more and 0.8 or less.
[0013] In the cutting step, it is preferable to use an abrasive having an average particle size of 100 μm or more and 170 μm or less.
[0014] In the cutting step, when a plurality of the titanium sintered bodies are stacked and cut together, it is preferable that the stack thickness of the plurality of the titanium sintered bodies is within the above thickness range. Effect of the Invention
[0015] According to the method for producing a porous titanium body of the present invention, the cut portions can have good properties and the titanium sintered body can be cut into various sizes and shapes in a comparatively short period of time. [Brief description of the drawings]
[0016] [Figure 1] 1 is an image showing a part of a plan view of a porous titanium body obtained by cutting in Comparative Example 1. [Diagram 2] 1 is an image showing a part of a plan view of a porous titanium body obtained by cutting in Comparative Example 2. [Diagram 3] 1 is an image showing a part of a plan view of a porous titanium body obtained by cutting in Example 1. [Figure 4] 1 is an image showing a part of a plan view of a porous titanium body obtained by cutting in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described in detail. A manufacturing method for a porous titanium body according to one embodiment of the present invention includes a cutting step in which, for example, a liquid injection device (abrasive jet device) is used to inject a liquid containing an abrasive toward a titanium sintered body obtained by sintering titanium powder or the like, thereby cutting the titanium sintered body. After the titanium sintered body is cut in the cutting step, a porous titanium body of predetermined dimensions and shape is obtained. Note that the manufacturing method for a porous titanium body according to this embodiment is mainly intended to cut out the porous titanium body by carrying out the cutting step.
[0018] The titanium sintered body is in the form of a sheet, has a thickness of 10 μm or more and 3000 μm or less, and a porosity of 30% or more and 55% or less. Such titanium sintered bodies are difficult to cut with a cutter or knife due to their material, thickness, and porosity. Therefore, in this embodiment, as described above, an abrasive jet process is adopted, which cuts the titanium sintered body by spraying a liquid containing an abrasive.
[0019] The abrasive to be sprayed toward the titanium sintered body has a Mohs hardness of 4.5 or more and 9.0 or less and an average circularity of 0.5 or more and 0.8 or less, in order to cut the titanium sintered body easily and in a short time while suppressing wear on the liquid spraying device. Also, from the viewpoint of avoiding problems in water electrolysis devices and the like due to contamination of the abrasive with the titanium porous body, the abrasive contains a total of 60 mass% or more of Si and / or Ti and O (oxygen), and the contents of Al, Fe, Ni, Mn, Cr and Cu are 5 mass% or less.
[0020] The titanium sintered body to be subjected to the cutting step may be obtained by purchasing, etc., but as one example, it can also be produced by carrying out a paste preparation step, a drying step, a binder removal step, and a sintering step in the following order.
[0021] (Paste preparation process) In the paste preparation step, a crushed powder such as titanium hydride / dehydrogenated powder or titanium hydride powder, or a spherical powder such as atomized powder, or other titanium powder, an organic binder, and an organic solvent are mixed using a mixer with an agitator, a rotary mixer, a triple roll mill, or the like to prepare a paste. At this time, the mixture may be crushed using a vibration mill, a bead mill, or other crushing mixer, or the like.
[0022] The average particle size of the titanium powder contained in the paste can be, for example, 75 μm or less, preferably 50 μm or less, also preferably 25 μm or less, and also preferably 18 μm or less. By using titanium powder with such a small particle size and dispersing it appropriately in the paste, a titanium sintered body with a smooth surface can be obtained. The average particle size of the titanium powder can be 5 μm or more, and even 10 μm or more. The average particle size means the particle size at which the cumulative distribution on a volume basis is 50% in the particle size distribution obtained by the laser diffraction scattering method.
[0023] As the organic binder used in the paste, various types can be appropriately selected and used, and examples thereof include methyl cellulose, polyvinyl alcohol, ethyl cellulose, acrylic, polyvinyl butyral, etc. An organic binder exhibiting hydrophobicity is preferable. However, it is not limited to the ones listed here. The organic solvent is, for example, alcohol (ethanol, isopropanol, terpineol, butyl carbitol, etc.). As an example, the organic binder may be polyvinyl butyral and the organic solvent may be isopropyl alcohol. The paste may further contain a plasticizer (glycerin, ethylene glycol, etc.), a surfactant (alkylbenzene sulfonate, etc.), etc.
[0024] The paste does not contain water as a solvent. It is preferable that the paste does not further contain a foaming agent. It is sufficient that the paste does not contain water as a solvent, and the inclusion of water that may be unintentionally mixed into the paste due to moisture absorption or the like is permitted. When a titanium sintered body is manufactured using a paste containing water and / or a foaming agent, large pores are formed during the manufacturing process, and the desired pore size cannot be realized. When a titanium porous body with large pores is manufactured by using a paste containing water and / or a foaming agent, the titanium porous body has poor surface smoothness that is likely to damage the electrolyte membrane of a solid polymer water electrolysis device.
[0025] (drying process) The paste is applied relatively thinly onto a substrate and then heated in a drying process, whereby the organic solvent in the paste is mainly evaporated, and a sheet-like molded product is obtained on the substrate.
[0026] The substrate is preferably a resin substrate, which is relatively inexpensive. In addition, the resin substrate has the advantage of being flexible and easy to handle. Specific materials for the resin substrate include polyesters such as PET (polyethylene terephthalate) and PEN (polyethylene naphthalate), and polyvinyls such as polyethylene, polypropylene, polystyrene, and polyvinyl alcohol. Among these, PET is preferable because it is inexpensive and the molded body can be easily separated from the substrate after the drying process.
[0027] It is optional to provide a release layer on the substrate, but when a release layer is provided, a silicone coating or the like can be used as the release layer. For example, a release layer can be provided on the substrate by selecting a substrate on which such a material has been applied in advance, such as Therapeel (registered trademark) manufactured by Toray Industries, Inc. By providing a release layer on the substrate, it becomes possible to easily separate the thin sheet-like molded body obtained after the drying process from the substrate.
[0028] In the drying step, the paste is dried on the mounting surface, for example, in an oven, a dryer, etc. This causes mainly the organic solvent in the paste to evaporate, and a sheet-like molded body is obtained on the substrate.
[0029] The heating temperature during drying can be 80°C or higher and 150°C or lower. By drying the paste at a temperature within this range, it is possible to complete the drying in a relatively short time while suppressing boiling of the organic solvent and other components in the paste. The drying time is not particularly limited and may be appropriately determined, and can be, for example, 5 minutes or longer and 300 minutes or shorter. It is preferable to perform the drying in an oxygen-containing atmosphere, for example, in the air atmosphere. This can suppress an increase in manufacturing costs.
[0030] (Debinding process) After the drying step is completed, the molded body is subjected to a binder removal step to volatilize the organic binder in the molded body.
[0031] In the binder removal step, for example, the molded body is preferably heated to a temperature of 320° C. or more and 450° C. or less. This makes it possible to remove the organic binder while suppressing sintering of the titanium powder due to heating.
[0032] The heating time is not particularly limited, but may be 3 hours or more and 12 hours or less. The atmosphere during heating is preferably an oxygen-containing atmosphere such as air atmosphere. When the atmosphere contains oxygen, it is possible to suppress the increase in cost that occurs when the atmosphere is strictly controlled.
[0033] (Sintering process) Thereafter, the compact that has been subjected to the binder removal step is subjected to a sintering step to sinter the titanium powder in the compact, thereby obtaining a titanium sintered body after the sintering step.
[0034] In the sintering step, the compact is heated to a temperature of, for example, 750°C to 1100°C. In the sintering step, the compact may be heated to the above temperature for a period of 1 hour or more and 4 hours or less. The sintering atmosphere may be, for example, 1.0×10-2 The atmosphere may be a vacuum or reduced pressure atmosphere of less than Pa, or an inert gas atmosphere of Ar or He.
[0035] The titanium sintered body to be subjected to the cutting step can be produced by a dry non-pressure deposition method in addition to the above-mentioned method involving the paste preparation step, drying step, binder removal step, and sintering step. In the non-pressure deposition method, for example, titanium powder is deposited on a setter made of graphite or the like, the upper side of the deposited titanium powder is rubbed off to form a sheet, and then the sheet-like deposited titanium powder is placed together with the setter in a heating furnace and sintered to obtain a titanium sintered body.
[0036] (cutting process) In the cutting step, a liquid containing an abrasive in powder form or particulate form is sprayed onto the titanium sintered body to cut the titanium sintered body. After cutting in the cutting step, a titanium porous body is obtained.
[0037] The titanium sintered body obtained by the above sintering step etc. is in the form of a sheet, and may have a thickness of, for example, 10 μm or more and 3000 μm or less per sheet. In the cutting step, the titanium sintered body of such a thickness can be cut well.
[0038] Alternatively, in the cutting step, multiple titanium sintered bodies may be stacked and cut at the same time. When multiple titanium sintered bodies are stacked and cut, a titanium porous body having a high straightness of the cut surface in a plan view is obtained. In this case, the number of stacked layers is adjusted so that the stacked thickness of the multiple titanium sintered bodies is 10 μm or more and 3000 μm or less. The thickness of the titanium sintered body referred to here means the total thickness when multiple titanium sintered bodies are stacked and cut.
[0039] From the viewpoint of obtaining a titanium porous body having better properties at the cut portions, the thickness of the titanium sintered body or bodies at the time of cutting is preferably 500 μm or more and 3000 μm or less, and even more preferably 500 μm or more and 2000 μm or less.
[0040] The thickness is measured at five points, four points on the periphery and one point in the center of a single sheet or multiple laminated sheets of titanium sintered compact, using a digital thickness gauge with a protruding probe and a minimum display of 0.001 mm (such as the digital thickness gauge (model number 547-321) manufactured by Mitutoyo Corporation), and the average of these measurements is used. When the sheet-like titanium sintered compact is rectangular in plan view, the four peripheral points mentioned above are the four corners.
[0041] Moreover, the titanium sintered body obtained by the above sintering process is composed of titanium powder particles bonded together, and has a three-dimensional mesh structure in which pores are formed between the bonded titanium powder particles. As an example, the titanium sintered body may have a skeleton with a three-dimensional mesh structure like titanium sponge. In many cases, the inside of the skeleton of the titanium sintered body, which is composed of titanium powder particles bonded together, is solid, not hollow. On the other hand, the three-dimensional mesh structure formed by bonding titanium fibers together is like a nonwoven fabric.
[0042] The porosity of the titanium sintered body is 30% or more and 55% or less. If the porosity is within this range, the titanium sintered body has the required air permeability or liquid permeability depending on the application, and can be used favorably as a porous transport layer of a solid polymer water electrolysis device. The porosity is preferably 35% or more and 50% or less, more preferably 35% or more and 45% or less.
[0043] When multiple titanium sintered bodies are stacked and cut, the porosity is the weighted average of the porosity weighted by the thickness of each sheet-like titanium sintered body. For example, assuming that two titanium sintered bodies are cut, the porosity Pw of the stacked titanium sintered bodies can be calculated by Pw = (P1 x T1) / (T1 + T2) + (P2 x T2) / (T1 + T2) when the porosity of each titanium sintered body is P1 and P2, respectively, and the thickness is T1 and T2, respectively. As an example, when two titanium sintered bodies are stacked, one with a thickness of 200 μm and a porosity of 30% and the other with a thickness of 200 μm and a porosity of 50%, the porosity of the stacked titanium sintered bodies is 40%.
[0044] The porosity ε of a single piece of titanium sintered compact is calculated by multiplying the apparent density ρ' calculated from the volume and mass of the titanium sintered compact, which are determined from the external dimensions such as width, length, and thickness, and the true density ρ (4.51 g / cm) of the titanium constituting the titanium sintered compact. 3 ) and calculate using the formula: ε = (1-ρ' / ρ) x 100.
[0045] If a titanium sintered body having the above-mentioned thickness and porosity is cut with a cutter or knife, the cut surface of the titanium porous body obtained after cutting may not be a neat straight line or curved line in a plan view, and irregular irregularities may be formed on the cut surface. This is thought to be because it is difficult to cut a titanium sintered body having a predetermined thickness and porosity with a cutter or knife. In addition, a cutter or knife may only be able to cut a titanium sintered body, which is difficult to cut in the first place, in a straight line, and the degree of freedom of the shape of the titanium porous body after cutting is low.
[0046] In contrast, in this embodiment, the titanium sintered body is cut by injecting a liquid containing an abrasive from a liquid injection device onto the titanium sintered body. The abrasive contained in the liquid has a Mohs hardness of 4.5 or more and 9.0 or less, and an average circularity of 0.5 or more and 0.8 or less. This allows the titanium sintered body, which has a certain degree of ductility, to be cut with high dimensional accuracy and prevents the occurrence of unevenness at the cut point. In addition, the injection mode of the liquid from the liquid injection device can be easily adjusted, so the titanium sintered body can be cut into various shapes. Furthermore, the time required for one cut is shorter than when a cutter or knife is used, and work efficiency is improved.
[0047] If the Mohs hardness of the abrasive is too low, the cutting ability of the injected liquid tends to be low, and good cutting of the titanium sintered body cannot be achieved. On the other hand, if the Mohs hardness is too high, for example, the nozzle of the liquid injection device will wear out, making it impossible to control the shape of the liquid injected from there, and as a result, it becomes difficult to control the dimensions of the cut titanium sintered body. In other words, if the Mohs hardness of the abrasive is set within a preferred range, the titanium sintered body can be cut with high dimensional accuracy, and the occurrence of unevenness at the cut point is suppressed. From this perspective, the Mohs hardness of the abrasive is preferably 5.0 or more and 8.5 or less, and more preferably 5.5 or more and 8.0 or less.
[0048] The Mohs hardness of an abrasive is measured at room temperature using a Mohs hardness tester on a lump sample having the same composition as the abrasive.
[0049] The lower the average circularity of the abrasive, the better the cutting ability of the titanium sintered body, but if it is too low, the abrasive will not flow well inside the liquid injection device, and the abrasive will not be contained in the injected liquid, which may make it impossible to cut the titanium sintered body. Therefore, the average circularity of the abrasive is preferably 0.5 to 0.7, more preferably 0.6 to 0.7.
[0050] The average circularity of an abrasive is measured, for example, by using a PITA-04 (manufactured by Seishin Enterprise Co., Ltd.), pouring abrasive particles together with a carrier liquid into a cell, taking images of a large number of particles with a CMOS camera, and measuring the perimeter (A) of the projected area of each particle and the perimeter (B) of a circle with an area equal to the projected area from 5,000 individual particle images to calculate the circularity, which is then determined as the average value of the circularity of each particle. The closer the particle shape is to a perfect sphere, the larger the circularity value, and a particle with a perfect sphere shape has a circularity of 1. Conversely, the further the particle shape is from a perfect sphere, the smaller the circularity value.
[0051] In order to cut the titanium sintered body with higher dimensional accuracy while smoothly flowing the abrasive in the nozzle of the liquid injection device, the average particle size of the abrasive is preferably 100 μm or more and 170 μm or less, and more preferably 130 μm or more and 160 μm or less. The average particle size of the abrasive is determined, for example, by using PITA-04 (manufactured by Seishin Enterprise Co., Ltd.), flowing the abrasive particles together with the carrier liquid into a cell, taking images of a large number of particles with a CMOS camera, measuring the diameter of a circle with an area equal to the projected area of each particle from 5,000 individual particle images, and calculating the circle equivalent diameter, which is the average value of the circle equivalent diameters of each particle.
[0052] The liquid ejection device may be any commonly available device, and the liquid may be water.
[0053] When an abrasive is added to a liquid and then sprayed onto a titanium sintered body together with the liquid, it may remain in the porous titanium body after cutting, for example by being captured in the three-dimensional mesh structure inside the porous titanium body. Even in this case, it is desirable to use an abrasive that can suppress adverse effects due to the elution of the abrasive inside the water electrolysis device when the porous titanium body is used as a porous transport layer of a solid polymer water electrolysis device.
[0054] From this viewpoint, the abrasive contains Si and / or Ti and O in total 60 mass % or more, and the contents of Al, Fe, Ni, Mn, Cr and Cu are 5 mass % or less.
[0055] The Si and / or Ti contained in the abrasive will not cause any problem even if they are mixed into the titanium porous body. The total content of Si and / or Ti and O in the abrasive is preferably 70 mass% or more, and 100 mass% or less. Specifically, soda-lime glass (Na2O-CaO-SiO2 system), titanium dioxide (TiO2), etc. can be suitably used as the abrasive.
[0056] Since Al, Fe, Ni, Mn, Cr, and Cu are elements that may cause contamination inside the water electrolysis device, it is desirable to avoid their inclusion in the titanium porous body as much as possible. When the abrasive contains one or more of the elements Al, Fe, Ni, Mn, Cr, and Cu, the content (the total content when more than one element is contained) is 5 mass% or less, preferably 3 mass% or less, and more preferably 2 mass% or less.
[0057] The content of components in the abrasive is measured using semi-quantitative analysis values obtained by EPMA analysis-ZAF method. For EPMA analysis, samples in which the abrasive is embedded in resin and polished are used.
[0058] When multiple titanium sintered bodies are stacked and cut, the surfaces (outer surfaces facing outward) of the top and bottom titanium sintered bodies can be covered with PET plates, etc., as necessary. Then, the multiple titanium sintered bodies sandwiched between the two PET plates can be fixed so as not to shift, and cutting can be started while they are immersed in water.
[0059] By spraying a liquid containing an abrasive as described above onto a titanium sintered body, a porous titanium body cut into a desired shape can be obtained.
[0060] The titanium porous body is made of titanium. If it is made of titanium, it can be said that the titanium porous body has high electrical conductivity at a certain relative density. The titanium content of the titanium porous body is preferably 97% by mass or more, and more preferably 98% by mass or more. The upper limit of the titanium content is not limited to this, but may be, for example, 99.8% by mass or less, or 99% by mass or less. This titanium content means the purity of titanium taking into account not only metal components but also impurities of gas components such as oxygen. Therefore, the titanium content can be calculated by subtracting the total content of impurities including metal components and gas components from 100% by mass.
[0061] The titanium porous body may contain Fe as an impurity, and may contain Ni, Cr, Al, Cu, Zn, and Sn as unavoidable impurities resulting from the manufacturing process. The Fe content may be, for example, 0.25 mass% or less. It is preferable that each of the contents of Ni, Cr, Al, Cu, Zn, and Sn is less than 0.10 mass%, and that the total content of these is less than 0.30 mass%. To measure the content of Fe and other elements in the titanium porous body, the titanium porous body is melted under an inert gas (argon gas, etc.) atmosphere to prepare a slab, which can be subjected to XRF analysis.
[0062] The oxygen content of the titanium porous body is not particularly limited, but may be 0.4 mass % or more and 2.0 mass % or less. The oxygen content can be measured by inert gas fusion-infrared absorption method.
[0063] The titanium porous body may have a purity equivalent to JIS H 4600 (2012) pure titanium class 1 to 4, typically class 1 or 2, excluding the carbon, nitrogen, and oxygen contents. In addition, the titanium porous body obtained by cutting the titanium sintered body in the above-mentioned cutting process often has the same characteristics, attributes, properties, etc. as the titanium sintered body. For example, the porosity, thickness, and skeleton of the three-dimensional network structure of the titanium sintered body and the titanium porous body often match. In addition, the titanium porous body obtained through the cutting process is often in a sheet shape. The sheet shape means a plate shape or foil shape whose thickness is small compared to the dimensions in a plan view, and the shape in a plan view is not particularly limited. EXAMPLES
[0064] Next, the method for producing a titanium porous body of the present invention was experimentally carried out, and its effects were confirmed, which will be described below, however, the description here is merely for illustrative purposes and is not intended to be limiting.
[0065] (Test Example 1) A titanium sintered body (WEBTi-K (WEBTi is a registered trademark) manufactured by Toho Titanium Co., Ltd.) measuring 300 mm in length, 300 mm in width, and 250 μm in thickness in plan view was cut to produce a titanium porous body measuring 100 mm in length, 100 mm in width, and 250 μm in thickness in plan view. The WEBTi-K is a sintered body of titanium powder, and has a skeleton with a three-dimensional mesh structure like that of a titanium sponge.
[0066] To cut the titanium sintered body, a manual knife was used in Comparative Example 1, and a roller cutter was used in Comparative Example 2. On the other hand, in Examples 1 and 2, a liquid (water) containing an abrasive was sprayed from a liquid spray device (OMAX2652 made by OMAX Corporation (USA)) to cut the titanium sintered body. The objects to be cut were a single titanium sintered body in Comparative Examples 1 and 2 and Example 1, and seven stacked identical titanium sintered bodies in Example 2. The seven titanium sintered bodies in Example 2 had a stacking thickness of 1750 μm. The porosity of the titanium sintered body was 40%, regardless of whether it was a single body or seven bodies.
[0067] In Examples 1 and 2, the abrasive used was soda-lime glass containing 70% or more by mass of Si and O, with a total content of Al, Fe, Ni, Mn, Cr and Cu of 2% or less by mass, a Mohs hardness of 6.5, an average circularity of 0.65 and an average particle size of 157 μm.
[0068] The results are shown in Figures 1 to 4. The numbers 149 μm, 274 μm, 78 μm, and 32 μm in Figures 1 to 4 refer to the straightness of the linear cut surface in a planar view, and were measured using an optical microscope (model number: VHX-S770) manufactured by Keyence Corporation as the total of the protruding amounts of the most protruding parts on both the left and right sides of a 5000 μm line segment.
[0069] In Comparative Example 1, cutting with a knife resulted in unevenness at the cut portion as shown in Fig. 1. In other words, the straightness of the cut surface was low. In Comparative Example 2, in which a roller cutter was used, the straightness of the cut surface was low as can be seen in Fig. 2.
[0070] In contrast, in Examples 1 and 2, no unevenness was visually observed at the cut portion, and the cut surface had high straightness. In particular, in Example 2, the cut surface had extremely high straightness. This is believed to be due to the increase in thickness caused by lamination. In other words, it is presumed that even if a single titanium sintered body having the same thickness as the lamination thickness is cut in the same manner, the cut surface will have similarly good properties.
[0071] In Comparative Examples 1 and 2, when an attempt was made to cut the titanium sintered body into a curved shape in a plan view, the curve was uneven (see FIG. 1), and the body could not be cut well. On the other hand, in Examples 1 and 2, the body could be cut into a good curved cut surface (see FIG. 4).
[0072] (Test Example 2) A total of four titanium sintered bodies were cut one by one in the same manner as in Example 1 of Test Example 1 above, except that a different abrasive was used.
[0073] The abrasive used here was made of silicon carbide (SiC), with a total content of Al, Fe, Ni, Mn, Cr and Cu of 2 mass% or less, a Mohs hardness of 13.0, an average circularity of 0.67 and an average particle size of 128 μm.
[0074] When the first piece of sintered titanium was cut, the dimensional accuracy of the porous titanium body after cutting (the deviation of the actual dimensions after cutting from the intended dimensions) was 0.1 mm, indicating that it was possible to cut with high accuracy.
[0075] After cutting the second and third pieces, the dimensional accuracy of the porous titanium after cutting was 0.5 mm, and the error had increased. After that, when the liquid injection device was inspected, it was found that the tip of the nozzle had been worn down. It was assumed that this had caused the liquid injection stream to become thicker, resulting in a decrease in dimensional accuracy. This was thought to be due to the use of an abrasive with a high Mohs hardness.
[0076] (Test Example 3) A titanium sintered body was cut in the same manner as in Example 1 of Test Example 1 above, except that a different abrasive was used.
[0077] The abrasive used here was soda-lime glass, containing 70% or more by mass of Si and O, and a total content of Al, Fe, Ni, Mn, Cr and Cu of 2% or less by mass (having the same composition as the soda-lime glass in Test Example 1), with a Mohs hardness of 6.5, an average circularity of 0.98 and an average particle size of 151 μm.
[0078] As a result, the cut portions of the titanium porous body had good properties, but compared to Example 1, the cutting operation took three times as long.
[0079] (Test Example 4) A titanium sintered body was cut in the same manner as in Example 1 of Test Example 1 above, except that a different abrasive was used.
[0080] The abrasive used here was made of garnet, had a total content of Al, Fe, Ni, Mn, Cr and Cu of 15 mass% or more, a Mohs hardness of 7.7, an average circularity of 0.70 and an average particle size of 125 μm.
[0081] As a result, the cut parts of the porous titanium body had good properties, but when this porous titanium body was used as a porous transport layer in a solid polymer water electrolysis device, elution of mainly Al and Fe was confirmed. This is thought to be due to the abrasive remaining in the porous titanium body, which eluted Al and Fe from the abrasive.
[0082] From the above, it has been found that according to the present invention, the cut portions can be made to have good properties and the titanium sintered body can be cut into various sizes and shapes in a comparatively short time.
Claims
1. A method for producing a titanium porous body, comprising the steps of: A cutting step of jetting a liquid containing an abrasive toward the titanium sintered body to cut the titanium sintered body, The titanium sintered body is in a sheet shape, has a thickness of 10 μm or more and 3000 μm or less, and has a porosity of 30% or more and 55% or less, A method for producing a titanium porous body, wherein the cutting step uses as the abrasive an abrasive containing Si and / or Ti and O in total 60 mass% or more, with Al, Fe, Ni, Mn, Cr and Cu contents of 5 mass% or less, a Mohs hardness of 4.5 or more and 9.0 or less, and an average circularity of 0.5 or more and 0.8 or less.
2. 2. The method for producing a porous titanium body according to claim 1, wherein an abrasive having an average particle size of 100 μm or more and 170 μm or less is used in the cutting step.
3. In the cutting step, the titanium sintered bodies are cut together in a stacked state, The method for producing a porous titanium body according to claim 1 or 2, wherein the thickness of the plurality of sintered titanium bodies is set within the range of thickness.
Citation Information
Patent Citations
Foreign matter detector for metal porous object, and metal porous object through foreign matter detection process
JP2008170197A
Metal porous body and method for manufacturing metal porous body
WO2020039693A1